Pension Reforms and the Opinions of European Citizens - Boeri, Tito; Boersch-Supan, Axel; Tabellini, Guido (American Economic Review, 2002)
This paper sheds light on the difficulties of pension reforms by analyzing the citizens´opinions on different aspects of the welfare state and its redistributive programs. We focus on the pension system, reporting the results of a questionnaire conducted in Germany and Italy in the Fall 2001. Our questionnaire was designed to shed light on the following issues: Are citizens aware of the unsustainability of the pension system and informed of its costs? Are reforms opposed by a majority or by a powerful minority? Which reform options seem politically more feasible and why? Which groups of citizens are more likely to favor reforms? We find that citizens are aware of unsustainability but lack information about the cost of the PAYG system. The status quo is a majoritarian outcome along many dimensions: most reform proposals lack a mojority and there is limited scope of packaging as reformers rarely support more than one reform option. Later retirement is the easier reform in Italy while opting-out of the PAYG system is popular in Germany, but only of accompanied by mandatory savings and with no transition burdan.